1996
DOI: 10.1086/177732
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Status of the Pre-protostellar Core L1498

Abstract: L1498 is a classic example of a dense cold pre-protostellar core. To study the evolutionary status, the structure, dynamics, and chemical properties of this core we have obtained high spatial and high spectral resolution observations of molecules tracing densities of 10(3)-10(5) cm-3. We observed CCS, NH3, C3H2, and HC7N with NASA's DSN 70 m antennas. We also present large-scale maps of C18O and 13CO observed with the AT&T 7 m antenna. For the high spatial resolution maps of selected regions within the core we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 0 publications
12
110
2
Order By: Relevance
“…Work carried out over the past decade has revealed that most inconsistencies between tracers result from chemical changes that occur in the gas at dense-core densities and, in particular, from the selective freeze-out of molecules onto cold dust grains (Kuiper et al 1996;Caselli et al 1999;Bergin et al 2002;Tafalla et al 2002;Aikawa et al 2005). As a result of this work, a reasonably consistent picture of the chemical behavior of the different gas tracers has emerged.…”
Section: Introductionmentioning
confidence: 87%
“…Work carried out over the past decade has revealed that most inconsistencies between tracers result from chemical changes that occur in the gas at dense-core densities and, in particular, from the selective freeze-out of molecules onto cold dust grains (Kuiper et al 1996;Caselli et al 1999;Bergin et al 2002;Tafalla et al 2002;Aikawa et al 2005). As a result of this work, a reasonably consistent picture of the chemical behavior of the different gas tracers has emerged.…”
Section: Introductionmentioning
confidence: 87%
“…The source coordinates were taken from Paper I and Levshakov et al (2013), except for L1498A, for which they were estimated from Fig. 3 in Kuiper et al (1996). The source L1498A is a gas condensation within the L1498 dark cloud separated by 2 from the NH 3 reference position.…”
Section: Observationsmentioning
confidence: 99%
“…Little et al 1979;Burke & Hollenbach 1983). This phenomenon is most obvious in dense and dark globules, in which abundances of molecules such as CO and CS can be decreased by one or two orders of magnitude towards the globule center (Kuiper et al 1996;Willacy et al 1998;Kramer et al 1999;Alves et al 1999;Caselli et al 1999;Bergin et al 2001;Jessop & Ward-Thompson 2001;Hotzel et al 2001;Hotzel et al 2002;Tafalla et al 2002). On the other hand, molecules frozen on the grain surfaces can be evaporated because of heating by energetic particles or radiation.…”
Section: Introductionmentioning
confidence: 99%